Growth and Yield of Sweet Sorghum (Sorghum bicolor L. Moench) in Tidal Swamp Land with Dolomite and Vermicompost Application - Yakup; Ria, Rofiqoh Purnama; Budianta, Dedik; Sumantri, Muhammad Haffidz (Journal of Smart Agriculture and Environmental Technology, 2024)
Sorghum (Sorghum bicolor L. Moench) plant is native to tropical and subtropical countries with high suitability for planting on marginal land. Therefore, this research aimed to determine the use of dolomite and vermicompost in tidal swamp soil for the growth and yield of sweet sorghum plants at the Experimental Garden and the Chemistry, Biology and Soil Fertility Laboratory, Department of Soil Science, Faculty of Agriculture, Sriwijaya University. A factorial randomized complete block design (FRCBD) consisting of two factors was used. The first factor was dolomite namely 0 ton.ha−1, 6 ton.ha−1, 9 ton.ha−1, and 12 ton.ha−1, while second factor was vermicompost including 0 ton.ha−1, 3 ton.ha−1, 6 ton.ha−1, and 9 ton.ha−1. The results showed that the application of Dolomite had a very significant effect on soil pH, N-total, P-available, and potassium exchangeability. In addition, dolomite increased plant height, number of leaves, chlorophyll content, fresh and dry weight shoot, number of grains, and weight of 1000 grains.